Mental health and wellbeing outcomes of climate change mitigation and adaptation strategies: A systematic review - Flores, Elaine C.; Brown, Laura J.; Kakuma, Ritsuko; Eaton, Julian; Dangour, Alan D. (Environmental Research Letters, 2023)
Abstract Climate change has already impacted the health and wellbeing of ∼5 billion people globally. However, the potential influence of climate change mitigation and adaptation strategies on mental health and wellbeing outcomes in low-and-middle-income countries (LMICs) remains insufficiently understood. We aimed to determine the effect of these strategies on mental health and wellbeing outcomes among LMIC beneficiaries. We carried out a systematic review to identify intervention and case studies published from 2013 to 2022, searching OVID Medline, Embase, PsycINFO, Global Health, Cochrane Library, GreenFile, Web of Science, and a subset of studies from the ‘Global Adaptation Mapping Initiative’ database. We included controlled, quasi-experimental, pilot, and focussed case studies reporting mental health or wellbeing outcomes assessments of climate change mitigation and adaptation strategies. We categorised studies by design, geographic region, target population, setting, environmental hazard, strategy type and primary outcomes. PROSPERO registry: CRD42021262711. A total of 9532 studies were initially retrieved, and 15 studies involving 12 255 participants met the inclusion criteria. Among these, twelve studies described evidence from single-adaptation strategies in nine LMICs, while three reported mitigation programmes. Only two randomised evaluations assessed common mental disorders such as depression, trauma or anxiety using validated scales. Most studies evaluated broader wellbeing at the community and individual levels. Nine studies (53.3%) reported significant beneficial changes in mental health or wellbeing outcomes among beneficiaries, while six (46.7%) obtained mixed results linked to local and sociocultural factors. The interventions ‘practical significance and overall impact remained unclear due to the heterogeneous reporting in program effectiveness, gaps in effect size assessments or qualitative insights. Our review highlights the scarcity and limited nature of the current evidence, underscoring the need for further equitable research. The ongoing global climate and mental health crises press us to fully understand and address these strategies’ psychosocial impacts and translate these findings into effective policy and transdisciplinary action as an opportunity to prevent and ameliorate significant, long-term problems in the population’s mental health and wellbeing.
openalex: W4389660070 KerkoCite.ItemAlsoKnownAs: 10.1088/1748-9326/ad153f 2129771:97VDTQLA 5072953:BLHNPA29
Keywords: openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged